2015
DOI: 10.1103/physreva.91.033621
|View full text |Cite
|
Sign up to set email alerts
|

Generic equilibration dynamics of planar defects in trapped atomic superfluids

Abstract: We investigate equilibration processes shortly after sudden perturbations are applied to ultracold trapped superfluids. We show the similarity of phase imprinting and localized density depletion perturbations, both of which initially are found to produce "phase walls". These planar defects are associated with a sharp gradient in the phase. Importantly they relax following a quite general sequence. Our studies, based on simulations of the complex time-dependent Ginzburg-Landau equation, address the challenge po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…where Lη 1 = 0, Lη 2 = η 1 and L is the linear operator from (11). Using orthogonality conditions, we arrive at the coupled system…”
Section: Weakly Nonlinear Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where Lη 1 = 0, Lη 2 = η 1 and L is the linear operator from (11). Using orthogonality conditions, we arrive at the coupled system…”
Section: Weakly Nonlinear Analysismentioning
confidence: 99%
“…At very low temperatures, phase slips can be caused by quantum fluctuations (aptly called quantum phase slips) [3][4][5] . Phase slips are not unique to superconductors, they also occur in superfluid systems [6][7][8] , and more recently, dissipation due to phase slips were studied in cold atom systems [9][10][11] . In particular, phase slips can be triggered in a superfluid cold atom system by a rotating weak link 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several theoretical works have treated the evolution of fermionic superfluids following a phase imprint [21,23,33,34] and the possible cascade scenarios following the decay of a planar dark soliton [22,23,35,36] via various mean-field approaches. In some of these works, it has been numerically found that, in a cylindrically symmetric potential with negligible dissipation, a planar soliton decays into a vortex ring, which then undergoes a long-lived oscillatory motion along the z axis [22,35,36].…”
mentioning
confidence: 99%
“…In some of these works, it has been numerically found that, in a cylindrically symmetric potential with negligible dissipation, a planar soliton decays into a vortex ring, which then undergoes a long-lived oscillatory motion along the z axis [22,35,36]. By mimicking experimental imperfections, such as trap distortions [21], and imperfect phase imprinting [23,34], later works found that the vortex ring further decays into a single remnant vortex. The proposed scenarios are, however, distinct from our observations.…”
mentioning
confidence: 99%
“…Note, that a realistic "onedimensional superconductor" is in fact a narrow strip with finite width W , much less than the Ginzburg-Landau coherence length ξ(τ ) ∝ (k B T c τ ) −1/2 , where τ = 1 − T /T c is the reduced temperature and T c the critical temperature. The energy dissipation in this system is related to phase-slip processes appearing in thin superconducting wires [4][5][6][7][8][9][10][11][12] or superfluids [13][14][15] , i.e., the processes of vortices/flux quanta crossing the strip.…”
Section: Introductionmentioning
confidence: 99%